Adhesive Wafer Bonding Using Ultra-Thin Spray-Coated BCB Layers. (8th September 2020) - Rimböck, Johanna; Gasiorowski, Jacek; Pires, Mariana; Zenger, Tobias; Burggraf, Jürgen; Dragoi, Viorel
Abstract : Permanent adhesive wafer bonding is a mature technology as it provides the advantages of a low thermal budget process and is less sensitive to the quality of the bonding surfaces. One of the most used materials for this process is Benzocyclobutene (BCB). Due to its usage the material was further developed for bonding applications. In this work we report the fabrication of ultrathin BCB bonding layers (down to 25 nm thickness) by means of spray coating. The advantages of such bonding layers are both technical (e.g. no substrates shift due to adhesive layer flow during bond process) or and economical (significantly lower material consumption compared to spin coating). The fabrication and characterization of such bonding layers is presented and bonding results are presented.